Multifunctional natural chlorogenic acid based nanocarrier for Alzheimer's disease treatment - Chenchen Wang; Xiaolei Song; Xiaowan Zhang; Peng Li; Wei Wei; Shihao Sun; Yong Chen (Materials Today Bio)
Alzheimer's disease (AD) presents significant challenges due to its intricate pathogenic mechanisms and the limited efficacy of single-target therapies. In this study, we investigated the potential of chlorogenic acid (CHA), a multifunctional natural active compound, in AD therapy by developing a trifunctional nanocarrier (MC-H/R/si). CHA was effectively conjugated with iron-based metal-organic frameworks (MIL/Fe-100) through chelation interaction. The resulting nanocomplex (MC) not only enhances the bioavailability of CHA but also facilitates a synergistic antioxidant effect between CHA and MIL/Fe-100. Importantly, CHA can chelate Zn2+ from β-amyloid/Zn2+ (Aβ/Zn2+) polymers, inhibiting Aβ aggregation. Furthermore, small interfering RNA targeting BACE1 was covalently linked to MC to downregulate BACE1 expression. Both in vitro and in vivo experiments revealed that MC-H/R/si effectively scavenges ROS, reduces inflammation and Aβ plaque, and improves the learning and cognitive abilities of APP/PS1 mice. These findings confirm that the trifunctional nanocarrier MC-H/R/si has great potential for AD treatment.